Quantifying the Probability of a Banking Crisis and the Implications for Sovereign Risk (International Journal of Applied Research in Management and Economics, 2020)
Identify and validate tools that anticipate the influence of macroeconomic indicators, whose history has indicated, at international level, episodes of economic collapse are the main objective of the paper. Using a logistic regression, I captured a model for quantifying the probability of banking crises, integrating indicators of the scoreboard on macroeconomic imbalances, as well as the sovereign risk premium for European countries. In this sense, the results show the premises underlying the elaboration of the analytical framework for the propagation of sovereign risk at the level of credit institutions.